Effect of Hydraulic Retention Time (HRT) and Organic Loading Rate (OLR) to the Nata de coco Anaerobic Treatment Eficiency and its Wastewater Characteristics - Istna Nafi Azzahrani; Fanny Arivia Davanti; Ria Millati; Muhammad Nur Cahyanto (agriTECH, 2018)
In this study, experiments were conducted to investigate the effect of hydraulic retention time (HRT) and organic loading rate (OLR) on process stability of nata de coco wastewater anaerobic treatment using semi-continuous digester. The standard-rate anaerobic digester with working volume of 8.5 L was used to investigate the effect of three different hydraulic retention times (15, 20, and 25 days), and a standard-rate anaerobic digester with working volume of 9.1 L was operated at different organic loading rates of 0.5, 1, and 1.5 g/L/day. The findings revealed that minimum HRT for nata de coco wastewater anaerobic treatment using semi-continuous digester was achieved at HRT 20 days. Based on data from this study, the reduction of organic content in nata de coco wastewater increased when OLR increased until 1 g/L/day. But then those parameters value decreased when OLR being increased further to 1.5 g/L/day. It showed that at 1.5 g/L/day the amount of substrate fed to the system was exceeding the total degradation capacity of methanogenic microorganisms, hence the organic overload happened and decreased the efficiency of organic content reduction in anaerobic treatment of nata de coco wastewater.